A novel locus for autosomal dominant congenital cerulean cataract maps to chromosome 12q - Berry, Vanita (Nature Publishing Group, 2011)
Cataracts are the commonest cause of blindness worldwide. Inherited cataract is a clinically and genetically heterogeneous disease that most often shows autosomal dominant inheritance. In this study, we report the identification of a novel locus for cerulean cataract type 5 (CCA5), also known as blue-dot cataract on chromosome 12q24. To date, four loci for autosomal dominant congenital cerulean cataract have been mapped on chromosomes, 17q24, 22q11.2–12.2, 2q33–35 and 16q23.1. To map this locus we performed genetic linkage analysis using microsatellite markers in a five-generation English family. After the exclusion of all known loci and several candidate genes we obtained significantly positive LOD score (Z) for marker D12S1611 (Z(max)=3.60; at θ=0). Haplotype data indicated that CCA5 locus lies within a region of 14.3 Mb interval between the markers D12S1718 and D12S1723. Our data are strongly suggestive of a new locus for CCA5 on chromosome 12.